Pós tratamento de efluente de laticínios para reuso potável por microfiltração e osmose inversa - Brixner, Eriton (2021)
The demand for natural resources in the world is growing, due to the monitoring of the development of society in general. In this respect, water, one of the most important resources for humanity, has not been used in the best available ways, which can generate future problems related to their availability and quality. One of the industrial segment that stands out in Brazil is dairy industry, and these are characterized by high water demand. This scenario adds to the high consumption of good quality water, subsequently returning to the environment an effluent that does not have potability characteristics. The objective of the research is to offer alternatives with a scientific basis for the reuse of these waters in the dairy industries. This, through the use of membrane separation processes, in this case more specifically, microfiltration and reverse osmosis. The first system used to purify the effluent was microfiltration, using a composite sample of treated raw effluent, leaving the ETE of a dairy. This system operates with a pressure between 0.2 and 0.4 bar. To feed the second purification system, reverse osmosis, 40 liters of effluent after microfiltration were needed. The operating characteristic of this is a pressure of 20 bar at 25°C. The results after the treatments were positives, getting water with good characteristics of color, conductivity and turbidity, requiring a correction of its pH, which became slightly acidic, ranging between 4.55 and 5.55. Thus achieving potability within the analyzed parameters.